COMBINED ANTIHYPERTENSIVE THERAPY EFFECTIVENESS IN ELDERLY PATIENTS WITH COGNITIVE DYSFUNCTION - A. P. Babkin; T. L. Kurbatova (Российский кардиологический журнал, 2011)
The dynamics of 24-hour blood pressure monitoring (BPM) and cognitive function parameters was assessed in 108 elderly patients with arterial hypertension (AH), who received combined antihypertensive therapy including Mexicor. All patients were randomized into three groups. Antihypertensive treatment included Mexicor in combination with either Ravel (indapamide), or Felodip (felodipine), or Lorista (losartan). Parallel groups were treated with Ravel, Felodip, or Lorista only, without Mexicor. Cognitive dysfunction and its dynamics were assessed by MMSE (Mini-Mental State Examination), clock drawing test, and Schulte test. The maximal beneficial dynamics of BPM parameters was observed for the combined therapy with Ravel and Mexicor, being slightly less pronounced for the combined therapy with Lorista and Mexicor, or Felodip and Mexicor. Target BP levels were achieved in 66,7%, 52,2%, and 47,6% of the patients, respectively. Adding a cytoprotector Mexicor to the complex antihypertensive therapy resulted in cognitive function improvement. The combination of Ravel and Lorista with Mexicor was associated with a significant improvement in cognitive function only in patients who achieved target BP levels, while the combination of Felodip and Mexicor improved MMSE scores in all patients, regardless of target BP achievement. Therefore, in elderly AH patients, the addition of a cytoprotector Mexicor to the complex antihypertensive therapy is associated with improved cognitive function.